Impact of the source of organic manure on persistence of E. coli O157:H7 gfp+ in rocket (Diplotaxis tenuifolia) and Swiss chard (Beta vulgaris cicla). (November 2017) - Hartmann, Rahel; Mogren, Lars; Rosberg, Anna Karin; Grudén, Maria; Vågsholm, Ivar; Olsson, Crister; Fricke, Andreas; Stützel, Hartmut; Alsanius, Beatrix
Abstract: The influence of organic nitrogen sources on the establishment of E. coli O157:H7 and the occurrence of other potentially human pathogenic bacteria on baby leaf salads was evaluated. Greenhouse-grown rocket and Swiss chard were spray-inoculated with gfp -tagged E. coli O157:H7 twice a week from when their first true leaves reached a length of 2 cm until three days before harvest. Analysis of nitrogen content in leaves revealed differences between treatments. Untreated plants had the lowest values, followed by plants fertilized with pig hair pellets and chicken manure. The same pattern was seen for the growth medium at the day of harvest. The applied strain showed similar establishment (measured using culture-dependent methods) irrespective of treatment, but Swiss chard hosted significantly more E. coli O157:H7 than rocket. Differences in the risk of infection were found for the crops, with plants fertilized with pig hair pellets showing a slightly higher risk. No relationship was found for total nitrogen content in leaves and colonization with E. coli O157:H7 gfp +. Isolating dominant Enterobacteriaceae from leaves, some strains showed conformity to bacterial species that have previously been identified to influence the establishment of E. coli O157:H7 in the phyllosphere. In this study, no inhibitory effects were observed in vitro . Colonies showing matching characteristics for Listeria spp. and Salmonella spp. were detected up to 5.5 and 5 log CFU g −1 fresh weight, respectively. However, presumptive Listeria spp. and Salmonella spp. could not be confirmed by sequencing of the 16S rRNA gene. Highlights: The probability of infection with E. coli O157:H7 differs for baby leaf items. Consumption of Swiss chard poses a higher risk of infection than rocket. Organic nitrogen sources affect the risk of infection.